Risk Factors Associated with The Incidence of Hypertension at the Productive Age (20-59 Years) in the Work Area of the Sikumana Public Health Center - Pedro P.L. Here; Pius Weraman; Helga J.N Ndun (Lontar : Journal of Community Health, 2022)
WHO shows that in 2015 there were about 1.3 billion people in the world suffering from hypertension. Riskesdas 2018 reports the percentage of hypertension nationally in Indonesia in adults or people aged over 18 years reaching 34.1%. This study aims to analyze the risk factors associated with the incidence of hypertension in the productive age (20-59 years) in the working area of ​​the Sikumana Health Center in 2020. This type of research is a quantitative study with a case-control study design. The case population in this study were all hypertensive patients of productive age recorded in the medical records of the Sikumana Health Center while the control population in this study were non-hypertensive patients recorded in the medical records who were neighbors of the case group. The sampling technique used is simple random sampling with a sample size of 84 people. The data analysis carried out was univariate analysis and bivariate analysis using a chi-square statistical test. The results of this study indicate that the risk factors associated with the incidence of hypertension in productive age (20-59 years) are genetic (p=0.000), obesity (p=0.001), stress (p=0.000), physical activity (p=0.000) ) and sodium (p=0.000), while the risk factors that were not associated with the incidence of hypertension in this study were gender (p=0.501) and smoking (p=1,000). People are expected to adopt a healthy lifestyle such as maintaining ideal body weight, doing regular physical activity or sports, managing stress, and reducing excess salt consumption. Keywords: hypertension, risk factors, productive age(20-59 years).